MicroRNA circulating in the early aftermath of motor vehicle collision predict persistent pain development and suggest a role for microRNA in sex-specific pain differences. Issue 1 (December 2015) - Linnstaedt, Sarah; Walker, Margaret; Parker, Joel; Yeh, Eunice; Sons, Robert; Zimny, Erin; Lewandowski, Christopher; Hendry, Phyllis; Damiron, Kathia; Pearson, Claire; Velilla, Marc-Anthony; O'Neil, Brian; et al.
Abstract Background Molecular mediators influencing the transition from acute to persistent musculoskeletal pain following common stress exposures such as motor vehicle collision (MVC) remain poorly understood. In this exploratory, proof of concept study, we compared circulating microRNA (miRNA) expression profiles in the early aftermath of MVC among individuals who did and did not subsequently develop persistent pain. Blood RNA samples were obtained from African American individuals (n = 53) who presented to the emergency department after MVC and were discharged to home after evaluation. The presence or absence of severe pain in the axial region, the most common and morbid region in which post-MVC pain occurs, was assessed 6 weeks following MVC via standardized questionnaire. miRNA expression was determined using miRNA-sequencing; nonparametric analyses were used to compare miRNA expression levels among individuals with and without persistent pain. Results Thirty-two mature miRNA were differentially expressed (p < 0.05) in those with and without severe axial pain at 6 weeks. miR-135a-5p, a regulator of the serotonin receptor that is known to be stress-responsive, differed most significantly between groups (p = 3 × 10−4 ). This miRNA, and miR-3613-3p (p = 0.001) survived correction for multiple testing (FDR = 0.15) in this small sample. Interestingly, differentially expressed miRNA were enriched for X chromosome location. In secondary analyses, the eight X chromosome miRNA were (a) more significantly associated with axial pain in women than men, (b) expressed more highly in the peripheral blood of women than men, and (c) predicted in pathway analyses (DIANA miRPath v 2.0) to regulate neuronal and neuroendocrine pathways previously implicated in various pain pathologies. Conclusions These results show that circulating miRNA predict persistent severe axial pain after MVC and suggest that they may be involved in the pathogenesis of post-traumatic musculoskeletal pain. However, further studies are needed to determine if these miRNA play a direct causal role.